The Feasibility of “Scanara” Ready-to-Wear Clothing with QR Code Technology - Novitasari, Neny; Nurmasitah, Sita (Universitas Negeri Semarang, 2025)
The development of digital technology has driven innovations in the fashion industry, including the integration of Quick Response (QR) codes into clothing products as an interactive information medium. This study aims to determine the feasibility of the design and products of the “Scanara